The p75 neurotrophin receptor is expressed by adult mouse dentate progenitor cells and regulates neuronal and non-neuronal cell genesis - Bernabeu, Ramon Oscar (2010)
The ability to regulate neurogenesis in the adult dentate gyrus will require further identification and characterization of the receptors regulating this process. In vitro and in vivo studies have demonstrated that neurotrophins and the p75 neurotrophin receptor (p75NTR) can promote neurogenesis; therefore we tested the hypothesis that p75NTR is expressed by adult dentate gyrus progenitor cells and is required for their proliferation and differentiation. In a first series of studies focusing on proliferation, mice received a single BrdU injection and were sacrificed 2, 10 and 48 hours later. Proliferating, BrdU-positive cells were found to express p75NTR. In a second series of studies, BrdU was administered by six daily injections and mice were sacrificed 1 day later. Dentate gyrus sections demonstrated a large proportion of BrdU/p75NTR co-expressing cells expressing either the NeuN neuronal or GFAP glial marker, indicating that p75NTR expression persists at least until early stages of maturation. In p75NTR (-/-) mice, there was a 59% decrease in the number of BrdU-positive cells, with decreases in the number of BrdU cells co-labeled with NeuN, GFAP or neither marker of 35%, 60% and 64%, respectively. These findings demonstrate that p75NTR is expressed by adult dentate progenitor cells and point to p75NTR as an important receptor promoting the proliferation and/or early maturation of not only neural, but also glial and other cell types.